Gastro-intestinal function and quality of life are favorable in adolescent and adult gastroschisis patients. (February 2020) - Snoep, Maartje C.; de Heus, Roel; Manten, Gwendolyn T.R.; Lap, Chiara C.M.M.; Snoeker, Barbara A.M.; Lindeboom, Maud Y.A.
Abstract: Background and aims: Studies on long-term sequelae of gastroschisis are scarce. The limited data suggest increased abdominal complaints in young children. To provide proper counseling for both parents and patients, more information on long-term outcome is needed. This study aims to evaluate long-term outcome regarding GI function, gastroesophageal reflux (GER), health-related quality of life (HRQoL) and cosmetic satisfaction. Methods: An observational longitudinal cohort study was performed. All patients ( N = 43) born between 1982 and 2008 with gastroschisis that were admitted to the University Medical Centre Utrecht, Wilhelmina Children's Hospital were invited to fill in a survey. Data of included patients were compared to validated Dutch reference standards. Results: Fourteen patients responded to the survey. The median follow-up was 18 years. Abdominal pain on weekly basis was present in two patients (14%) and feeding difficulties were present in one patient. Presence of a complication during gastroschisis treatment led to more GI symptoms (80% versus 22%). One patient experienced moderate complaints of regurgitation or dyspepsia. Although the overall HRQoL was lower in teenage gastroschisis patients as compared to healthy controls (73/100 versus 83/100, respectively), we found no relevant difference in overall HRQoL in the other age groups. Seven patients (50%) were satisfied with the cosmetic result of the scar. Conclusions: GI function and HRQoL in gastroschisis patients seem similar to healthy controls at adolescent and adult age. Complications during gastroschisis treatment led to an increase of abdominal complaints later in life. The surgical technique had no significant effect on the cosmetic results. Highlights: Gastroschisis patients have normal gastro-intestinal functioning at adolescent and adult age. Gastroschisis patients with complications during their treatment have more abdominal complaints later in life. Health-related quality of life is favorable in gastroschisis patients at adolescent and adult age. Half of the gastroschisis patients is satisfied with the cosmetic result of their scar.